Past and present foodscapes of a traditional fermented milk, mabisi, in three Zambian regions. - Taonga Chirwa-Moonga; Elise F Talsma; Himoonga Bernard Moonga; Bas J Zwaan; Sijmen E Schoustra; Wilfred Dolfsma (PLoS ONE)
Food serves not only as a source of individual physical sustenance but also a central element in shaping social relationships and culture within families and communities. The concept of foodscapes has emerged as a valuable framework for understanding the intricate connections between food, the environment, and society, highlighting both the physical and cultural dimensions of food. Production and consumption practices of traditional healthy foods, such as the Zambian traditional fermented milk mabisi, evolve over generations, a process influenced by the foodscape they are embedded in. Foodscapes can evolve as a result of several different developments, including migration, acculturation, and urbanization. This paper aims to utilize the concept of foodscape to understand why certain groups of individuals adopt diets incorporating mabisi while others do not. Additionally, the study identifies drivers of healthy food consumption within the broader foodscape. Adopting a qualitative approach using semi-structured interviews, along with purposive and snowball sampling, a total of 86 participants that differ in mabisi production and consumption were sampled from Southern, Eastern, and Western provinces of Zambia. Using thematic analysis, we found that individuals' dietary choices were influenced by their ethnic origins and the evolving foodscape. Traditional food production practices were replaced by modern food production techniques, shifting from the use of traditional calabashes for mabisi production to plastic containers. Access to healthy indigenous foods has also diminished and because of urbanization and environmental degradation, wild roots, fruits, bushmeat and vegetables were no longer as readily available as before. Understanding the foodscape of a healthy traditionally fermented food such as mabisi, its elements, and its evolution over time, may provide insights that would promote the consumption of healthy traditional foods.